‘Instead of fetching flowers, the youths brought in flakes of snow’: exploring extreme weather history through English parish registers - Veale, Lucy; Bowen, James P.; Endfield, Georgina H. (Taylor and Francis, 2017)
Parish registers provide organized, dated and located population data and as such, are routinely among the most frequently consulted documents within the holdings of county record offices and archives. Throughout history, extreme weather has had significant impacts on the church, its congregation, and local landscape. It is for these reasons that extreme weather events have been deemed worthy of official note by authors of many registers. Although isolated entries have been used as supporting evidence for the occurrence of a number of historic extreme weather events, the information that parish registers contain relating to weather history has not been studied in its own right. Parish register narratives add new events to existing chronologies of extreme weather events and contribute to our understanding of their impacts at the local level. As public and well used documents they also function to keep the memory of particular events alive. The examples in this paper cover a wide range of weather types, places, and time periods, also enabling recording practice to be explored. Finally, as the number of digitized registers increases, we highlight the risks of weather narratives being obscured, and reflect on how the weather history contained within might be systematically captured.